Analisis Kinerja Keuangan dengan Profit Sensitivity Analysis Pada Perusahaan Telekomunikasi di Indonesia - Nur Fadhilah Ahmad Hasibuan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
This study aims to analyze financial performance using the profit sensitivity analysis approach of telecommunications companies listed on the Indonesia Stock Exchange in the period of 2016 to 2019. This type of research is quantitative descriptive. The sampling technique used was purposive sampling. The data used secondary data in the form of financial statements of telecommunications companies listed on the Indonesia Stock Exchange. This study was analyzed using the profit sensitivity analysis approach. The results of this study indicate that for asset management, the best company in improving the performance of the company is PT. Telkom, Tbk. Furthermore, liability management is proxied by leverage management, a company that shows excellent financial performance owned by PT. Telkom, Tbk. Then for overall management, companies that are able to improve their financial performance are PT. Telkom, Tbk. The conclusion of this research is PT. Telkom, Tbk has the best financial performance between the two other large companies